"LuXurY" hotel loyalty – a comparison of Chinese Gen X and Y tourists to Macau. Issue 7 (12th October 2015) - Yang, Fiona X.; Lau, Meng-Chan (Virginia) Meng-Chan
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose; – This study aims to investigate generational disparities of Chinese Generation (Gen) X and Y tourists by examining their loyalty determinants in a luxury hotel setting. Design/methodology/approach – A survey of five-star hotel guests in Macau yielded 285 complete responses. Structural equation modeling was used to test the quality-loyalty framework through the mediating roles of perceived value and satisfaction, with a multi-group comparison to examine generational differences. Findings – The results indicate that top quality rooms and services are high on the agenda of both generations, while Gen X places more weight on convenience and food and Gen Y on security; satisfaction does not induce loyalty, whereas value fully or partially mediates the quality-loyalty relationship; and Gen X is value-centered in building loyalty, yet Gen Y exhibits both value consciousness and stronger demands for upscale quality features. Practical implications – The findings help hotel managers cater to different generations by improving determinant attributes of service quality and enhancing hotel value. Originality/value – The study makes noteworthy contributions to the generational differences of Chinese tourists and sheds light on future research in tourism and hospitality to explore the characteristics of young generations.